VULGAR TYPOLOGIES, SOCIAL EQUILIBRIUM, AND MORAL ETHICS IN YORUBA PROVERBS - Coker, Oluwole (Proverbium - Yearbook, 2016)
Proverbs are essential tools of elucidating and expounding social issues. They express the innate principles and ethics of any given society. Among the Yoruba of south-western Nigeria, proverbs occupy a strategic place among other orature forms, as the warehouse of indigenous knowledge. This paper examines the representation of vulgarism in Yoruba culture by analyzing twenty-five purposively selected proverbs sourced mainly from the researcher’s collections as a paremiographer and as a member of the Yoruba ethnic and linguistic group, as well as from existing secondary sources. The selected proverbs are chosen because they harp on the act of sex and direct reference to coition or the sexual organs. Hence, vulgar archetypes are examples of didactic aesthetics, moral education and sexuality consciousness among the Yoruba, in a unique way.